Money as a Tool for Collective Action - Giacomo Bazzani (Partecipazione e Conflitto, 2020)
Complementary currencies are usually seen as a by-product of collective movements for social change or as an institutional tool for local development: they are an outcome of collective action, not the origin of collective mobilisation. Empirical research on the Sardex complementary currency, though, suggests that money may support the emergence of collective action. Traditional economic theory considers any collective benefits provided by the economic system as the secondary effects of individual entrepreneurs seeking to maximise their profits. Entrepreneurs belonging to the Sardex network, though, do associate the use of the Sardex currency with direct collective benefits. This means they consider their business activities to be a form of collective action for promoting the common good of Sardinia's socio-economic development. Using the Sardex currency sets this collective action in motion: some Sardex members also work to expand the Sardex network without any expectation of economic gain.